Investigation of Wear Behavior of Particle Reinforced AL/B4C Composites under Different Sintering Conditions - İsmail Topcu (Tehnički Glasnik, 2020)
In this study, the effects of different sintering conditions of boron carbide reinforced to aluminum matrix powder on microstructure, density and wear resistance by a mechanical alloying method were researched. Powders produced by mechanical alloying for eight hours at the atrial shaft were compressed with a cold isostatic press die under 350 MPa to obtain cylindrical composite specimens. The raw samples were sintered in high purity argon at 600, 625, 650 °C for 90 minutes. The wear behavior of the Al/B4C metal matrix composite was studied using a pin-on-disk wear tester. Under favorable conditions, it has been observed that reinforced boron carbide wear can be reduced by more than two decades. Various investigations have been made to relate this improved wear performance to reinforcement ratios. Aluminum abrasion test results showed that different types of abrasion occurred and that the abrasion resistance was increased by the change of the bubble rate. In the experimental studies that were carried out, it was observed that wear resistance increased with the proportion of boron carbide reinforced directly by the weight, and especially with a 15% B4C ratio depending on the increased reinforcement ratio.